Comparative Suitability of Various Growth Media for Producing Cucumber Transplants: Suitability of Growth Media for Producing Cucumber Transplants - Atif, Muhammad Jawaad; Jellani, Ghulam; Malik, Muhammad Humair Ahmed; Saleem, Noor; Akram, Atif; Javed, Ahsan (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2016)
Peat is generally used as a medium for growing cucumber, which is highly expensive.Many wastes which are useless by-products of vegetables production process can be useful as organic materials with potential applications. These wastes can be used as alternatives to peat. The study was conducted in a plastic house at Directorate of Vegetable, Department of Horticultural Research &Development, National Agricultural Research Centre, Islamabad. Peat, compost and farmyard manure alone and in combination were compared for producing cucumber seedlings. Maximum germination (96.33%), seedlings shoot length (28.33 cm), seedling height (38.67 cm), seedling vigor index (38.67) and minimum days to emergence (16.33) were found in T9 (peat, compost and Traditional practicing media in 1:1:1 ratio). Maximum dry matter accumulation (38.50 %) was recorded in T4 (Peat and compost, in 1:1/2 ratio) and maximum benefit cost ratio (1.87) was recorded in T2 (compost).